Stress-testing a quasi-market: Unintended consequences of the Swedish school voucher system - Andreas Bergh; Joakim Wernberg (Research Institute of Industrial Economics (IFN), 2024)
Quasi-markets in the provision of public services are increasingly common but also highly contested. We formulate a conceptual framework based on economic theory to describe how quasi-markets differ from traditional markets in five aspects: 1) revenues, costs, and profits, 2) the matching of supply and demand, 3) competition, 4) structural change, and 5) rent-seeking. Using the assumption of profit-maximizing actors, we provide a stress test of quasi-market design and highlight how these differences affect incentives and expected outcomes. Applying the framework to the Swedish school voucher system, we show how design decisions have generated unintended consequences that are detrimental to service quality and run counter to policy goals.
Keywords: H52; H83; D47; 330; quasi-markets; school vouchers; market structure; public administration